2016
DOI: 10.18632/oncotarget.11178
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol counteracts lipopolysaccharide-induced depressive-like behaviorsviaenhanced hippocampal neurogenesis

Abstract: Radial glial-like cells (RGLs) in the adult dentate gyrus (DG) function as progenitor cells for adult hippocampal neurogenesis, a process involved in the stress-related pathophysiology and treatment efficiency of depression. Resveratrol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 58 publications
1
63
0
Order By: Relevance
“…Neuroinflammation has been proved to play an important role in depression. As previous studies suggested, related signaling pathway of inflammation has been proved to be highly associated with depression disease (29,30). Thus, we further explored the molecular link between inflammation and depression.…”
Section: Discussionmentioning
confidence: 85%
“…Neuroinflammation has been proved to play an important role in depression. As previous studies suggested, related signaling pathway of inflammation has been proved to be highly associated with depression disease (29,30). Thus, we further explored the molecular link between inflammation and depression.…”
Section: Discussionmentioning
confidence: 85%
“…Further evidence suggest that it is the dorsal hippocampus that is involved in spatial learning and memory, while the ventral hippocampus is more associated with limbic functions (Brooker, Gobeske, Chen, Peng, & Kessler, ; Hyer, Hunter, Katakam, Wolz, & Glasper, ; Kheirbek & Hen, ; Loxton & Canales, ; McHugh, Fillenz, Lowry, Rawlins, & Bannerman, ; Schoenfeld, McCausland, Sonti, & Cameron, ). Abnormalities in hippocampal function are associated with various neurological and psychiatric disorders in adults such as anxiety, schizophrenia and depression (Ampuero, Jury, Hartel, Marzolo, & Zundert, ; Brooker et al, ; Caruncho et al, ; Danzer, Kotloski, Walter, Hughes, & McNamara, ; Liu et al, ; Perez‐Domper et al, ; Yun et al, ).…”
Section: Locations Of Adult Neural Stem Cells In the Mammalian Brainmentioning
confidence: 99%
“…For example, the dorsal hippocampus appears to be involved in spatial learning and memory, while the ventral hippocampus is associated with stress, emotion and affect (Brooker et al, ; Hyer et al, ; Kheirbek & Hen, ; Loxton & Canales, ; McHugh et al, ; Schoenfeld et al, ). The hippocampus appears to have important functions in neurological and psychiatric disorders including anxiety, schizophrenia and depression (Ampuero et al, ; Brooker et al, ; Caruncho et al, ; Danzer et al, ; Liu et al, ; Perez‐Domper et al, ; Yun et al, ). Lesions in the ventral hippocampus and specifically ventral dentate gyrus lesions in rodents produce decreased anxiety‐like behaviour (Cameron & Glover, ).…”
Section: Functional Aspects Of New Dgcs In the Adult Hippocampusmentioning
confidence: 99%
“…The TST was performed according to previously reported methods. 24,25 Mice were suspended by a mounted hook 50 cm above the floor using adhesive tape, which was placed ~1 cm from the tip of the tail. The activities of mice were recorded for 6 min.…”
Section: Tail Suspension Test (Tst)mentioning
confidence: 99%